Natural Selection Footprints Among African Chicken Breeds and Village Ecotypes - Elbeltagy, Ahmed R.; Bertolini, Francesca; Fleming, Damarius S.; Van Goor, Angelica; Ashwell, Chris M.; Schmidt, Carl J.; Kugonza, Donald R.; Lamont, Susan J.; Rothschild, Max. F. (Frontiers in Genetics, 2019)
Natural selection is likely a major factor in shaping genomic variation of the African indigenous rural chicken, driving the development of genetic footprints. Selection footprints are expected to be associated with adaptation to locally prevailing environmental stressors, which may include diverse factors as high altitude, disease resistance, poor nutrition, oxidative and heat stresses. To determine the existence of a selection footprint, 268 birds were randomly sampled from three indigenous ecotypes from East Africa (Rwanda and Uganda) and North Africa (Baladi), and two registered Egyptian breeds (Dandarawi and Fayoumi). Samples were genotyped using the chicken Affymetrix 600K Axiom® Array. A total of 494,332 SNPs were utilized in the downstream analysis after implementing quality control measures. The intra-population runs of homozygosity (ROH) that occurred in >50% of individuals of an ecotype or in >75% of a breed were studied. To identify inter-population differentiation due to genetic structure, FST was calculated for North- vs. East- African populations and Baladi and Fayoumi vs. Dandarawi for overlapping windows (500 kb with a step-size of 250 kb). The ROH and FST mapping detected several selective sweeps on different autosomes. Results reflected selection footprints of the environmental stresses, breed behavior, and management. Intra-population ROH of the Egyptian chickens showed selection footprints bearing genes for adaptation to heat, solar radiation, ion transport and immunity. The high-altitude-adapted East African populations’ ROH showed a selection signature with genes for blood circulation, oxygen-heme binding and transport. The Neuroglobin gene was detected on a Chromosome 5 ROH of Rwanda-Uganda ecotypes, and the Sodium-dependent noradrenaline transporter, SLC6A2 on a Chromosome 11 ROH in Fayoumi breed and may reflect its aggressive behavior. Inter-population FST among Egyptian populations reflected genetic mechanisms for the Fayoumi resistance to Newcastle Disease Virus (NDV), while FST between Egyptian and Rwanda-Uganda populations indicated the Secreted frizzled related protein 2, SFRP2 (Chromosome 4), that contributes to melanogenic activity and most likely enhances the East African chicken adaptation to high-intensity of UV solar radiation at higher altitude near the equator. These results enhance our understanding of the natural selection forces role in shaping genomic structure for adaptation to the stressful African conditions.